Rischio di impresa e responsabilità civile La tutela dell'ambiente tra prevenzione e riparazione dei danni - Francesca Degl'Innocenti (Premio Ricerca «Città di Firenze», 2013)
The volume analyses the theme of "business risk" with an original and interdisciplinary approach from a dual point of view: the control and internal management of risks by the company, and the criteria for imputing liability for damages relating to the carried out activity. On the first point, consideration is given to the obligations of preparing adequate organizational models to prevent damage, even in situations of "unknown technology", and initiatives aimed at encouraging "socially responsible" conduct, such as ethical codes. On the other point, there are the problems relating to the most effective civil liability models to allocate the cost of harmful events on the subject who created the relative risk and not on the victim who suffers from them or on the community. In the second part of the volume, the topic is addressed with particular reference to the environment sector, which is the most profitable and also the current laboratory for testing the interconnections between prevention and fixing, conduct obligations and rules of responsibility, to the extent that the economic costs are charged to the operator in order to prevent, reduce or eliminate damage to the environment.